2009
DOI: 10.1366/000370209787169885
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Surface Analysis Using a Newly Developed Thin-Sample Preparation System

Abstract: We developed a new sampling system, the Nano Catcher, for measuring the surface chemical structure of polymers or industrial products and we evaluated the performance of the system. The system can directly pick up surface species whose depth is on the order of approximately 100 nm and can easily provide a sample for a Fourier transform infrared (FT-IR) system without the necessity of passing it over to a measurement plate. The FT-IR reflection data obtained from the Nano Catcher were compared with those obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A mirror-polished SUS 304 substrate was coated with a SiCN film with a thickness of about 280 nm. The adhesion strength and film structure of a SiCN film with a thickness of about 100 nm deposited on Si(100) were measured by surface-interface physical property analysis equipment (DAIPLA WINTES Corp., SAICAS BN-1) [10,11] and determined using Fourier transform infrared (FTIR) spectroscopy, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A mirror-polished SUS 304 substrate was coated with a SiCN film with a thickness of about 280 nm. The adhesion strength and film structure of a SiCN film with a thickness of about 100 nm deposited on Si(100) were measured by surface-interface physical property analysis equipment (DAIPLA WINTES Corp., SAICAS BN-1) [10,11] and determined using Fourier transform infrared (FTIR) spectroscopy, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling method has been described in our previous papers. 1,2 The sample surface was shaved to the input shaving depth, and the shaving depth and vertical load on the blade surface were monitored. It was possible to retain the cutting piece on the front surface of the blade by controlling the cutting speed and depth.…”
Section: Experimental and Calculusmentioning
confidence: 99%
“…The changes in the molecular conformations of bisphenol A polycarbonate (BPAPC) after supplying a shear force field were monitored by a very thin surface preparation system. 1,2 Robertson 3 proposed a theory to describe how shear stress can induce structural changes in a glassy polymer, decreasing the rigidity of the glass and allowing the polymer flow. He also demonstrated that a shear force field could induce a structural state characteristic of the polymer at temperatures above the glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported an attempt to develop a system to obtain qualitative information by surface chemical structure analysis using FT-IR directly. 2 The technique can detect a very thin surface region of ∼100 nm in depth; therefore, the technique is much more sensitive than ATR in terms of analysis of very thin surface layers since the penetration depth of the evanescent wave in the ATR configuration is ∼ 1 μm. A detailed description of the technique named the “Nano Catcher” (NC) was given in our previous paper.…”
Section: Introductionmentioning
confidence: 99%